ANALISIS PERSAINGAN USAHA INDUSTRI TEPUNG SAGU DI KECAMATAN MERBAU KABUPATEN KEPULAUAN MERANTI - M, Surbakt Agus; Jahrizal, Jahrizal; Eka, Pailis Armas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to see the business competition in the sago flour industry in Merbau District, Kepulauan Meranti Regency. The Population and sampel in this study were the sago flour industry in Merbau, which may have 11 business units. Th data used in this study are primary data and secondary data. Primary data is data that comes from questionnaires and secondary data used is data obtained from the Department of Industry and Trade of Meranti Islands Regency in 2014-2018. The research used descriptive and quantitative analysis to see the competitive conditions of the sago flour industry in Merbau District, Kepualauan Meranti Regency. The analytical test tool used in this research is the Market Structure, CR4, IHH, and Porter’s analysis. The Results of the market structure study showed that CR4 51,62 % is included in the middle to lower market category of monopolistic competition or lose oligopoly markets. And the Herfindahl-Hirchman Indeks value shows this 1,045,95 is included in the category of effective competition or monopoly market. The results of the porter analysis show that the competitive condition of the sago flour industry in Merbau District, Meranti Islands Regency is quite high. This is because there are still many sago flour industries and sago flour that do not have business licenses. From the low supplier variable, the sago flour industry has a fairly high number of buyers, namely 10-25 consumers per day. The newcomer variable is slow, because the number of sago flour industries in the last 5 years has had 3 new business. And for the substitution variable for the sago flour industry in Merbau Regency, there are 6 sago flour industries that do not have a business license.Key Words: Industrial Competition, Sagu Flour, CR4, IHH, Porter